PERANAN PRIMA TANI TERHADAP PENDAPATAN PETANI PADI SAWAH (Oryza sativa L.) DI DESA SULILIRAN BARU KECAMATAN PASIR BELENGKONG KABUPATEN PASER - Wahyu Gangsar Suseno; Tetty Wijayanti (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2008)
The purpose of this research was to know: the difference of farmer’s income between before and after being held of Primatani. The research is conducted in Suliliran Baru Village, Pasir Belengkong sub district, Paser regency from November 2007 to Januari 2008. T-test is used to find the different of farmer’s income. The results of this research was significantly different of farmer’s income. Between before and after being held Primatani indicated by t-value = 2,26 > t-tabel = 2,042. Key words : Primatani Program, farmer’s income